KONSEPSI UANG DAN KEBIJAKAN MONETER PERSPEKTIF IBNU TAIMIYAH - Fageh, Ahmad (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2018)
Islam is a religion other than syumuliyah (perfect) also harakiyah (dynamic). Called perfect because Islam is the perfect religion of previous religions and shari'at regulate all aspects of life, both aqidah and muamalah. In the rule of muamalah, Islam regulates all forms of human behavior in dealing with each other to meet the needs of his life in the world. These include the Islamic rules governing Money and Monetary Policy. Seeing the importance of Money in Islam is even used as an official means of exchange around the world, the discussion of this theme becomes very interesting and urgent.Long before the economic thinking of experts on Money and Monetary Policy, the Islamic world had earlier had a figure who was concerned in this field. He is IbnTaymiyyah, a famous Muslim scholar. This paper will try to compile some of his thoughts on Money and Monetary Policy